Evidence for climate-driven synchrony of marine and terrestrial ecosystems in northwest Australia - Ong, J.; Rountrey, A.; Zinke, Jens; Meeuwig, J.; Grierson, P.; O'Donnell, A.; Newman, S.; Lough, J.; Trougan, M.; Meekan, M. (Blackwell Publishing, 2016)
© 2016 John Wiley & Sons Ltd. The effects of climate change are difficult to predict for many marine species because little is known of their response to climate variations in the past. However, long-term chronologies of growth, a variable that integrates multiple physical and biological factors, are now available for several marine taxa. These allow us to search for climate-driven synchrony in growth across multiple taxa and ecosystems, identifying the key processes driving biological responses at very large spatial scales. We hypothesized that in northwest (NW) Australia, a region that is predicted to be strongly influenced by climate change, the El Niño Southern Oscillation (ENSO) phenomenon would be an important factor influencing the growth patterns of organisms in both marine and terrestrial environments. To test this idea, we analyzed existing growth chronologies of the marine fish Lutjanus argentimaculatus, the coral Porites spp. and the tree Callitris columellaris and developed a new chronology for another marine fish, Lethrinus nebulosus. Principal components analysis and linear model selection showed evidence of ENSO-driven synchrony in growth among all four taxa at interannual time scales, the first such result for the Southern Hemisphere. Rainfall, sea surface temperatures, and sea surface salinities, which are linked to the ENSO system, influenced the annual growth of fishes, trees, and corals. All four taxa had negative relationships with the Niño-4 index (a measure of ENSO status), with positive growth patterns occurring during strong La Niña years. This finding implies that future changes in the strength and frequency of ENSO events are likely to have major consequences for both marine and terrestrial taxa. Strong similarities in the growth patterns of fish and trees offer the possibility of using tree-ring chronologies, which span longer time periods than those of fish, to aid understanding of both historical and future responses of fish populations to climate variation.